Design of automatic control-based pneumatic system for material thickness measurement - Alfian Ady Saputra; Dan Mugisidi; Riyan Ariyansah (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
TThe manual measurement of materials using pneumatic systems for inspections remains prevalent, posing challenges in meeting the demands and speed of modern production processes. To address this, there is a critical need for an automated inspection tool capable of generating a significant number of inspection inputs. This research objectives to design and implement an automatic thickness inspection system, employing pneumatic technology and inductive proximity sensors. The study adopts an experimental research design, systematically progressing through literature review, algorithm design, PLC programming, and comprehensive testing. The pneumatic system, known for its high response speed and durability, is capable of accurately measuring material thickness and sorting items with precision. The integration of inductive proximity sensors enhances the system's efficiency in detecting both metallic and non-metallic objects. The research findings reveal a system effectiveness of 95.8% in the initial test and 91.7% in the subsequent test. Notably, deviations in the Ø12 sensor are identified in detecting NG minus material. Despite this, the system's overall effectiveness surpasses the 90% threshold, meeting stringent standard criteria. The study concludes with insights into the identified deviations and underscores the system's effectiveness in meeting high-standard criteria. Recommendations for improvement include modifications to the stopper or proximity sensor position, sensor recalibration, continuous monitoring, and material path separation